SISTEM INFORMASI PENDISTRIBUSIAN BARANG PADA PT. SAMPURNA SUKSES UTAMA ACEH BESAR - Hasanah, Uswatun (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2020)
Goods Distribution Information System is one of the data processing activities at PT. Sampurna Sukses Utama Aceh Besar, to get information about the distribution of goods to be more directed and easily obtained. In this study, the authors only discuss the problem of goods distribution and data management mechanisms of PT. Sampurna Sukses Utama Aceh Besar and designed the Information Distribution System for PT. Sampurna Sukses Utama Aceh Besar by using Visual BASIC.NET. The purpose of writing is to understand the problem of Information Systems Distribution of Goods at PT. Sampurna Sukses Utama Aceh Besar as well as making aids application on the Information System of Goods Distribution at PT. Sampurna Sukses Utama Aceh Besar uses Microsoft Visual BASIC.NET. Data collection needed in writing this report was obtained by two methods, namely a literature study relating to the literature of library books and other scientific works, field studies by carrying out interviews, and direct observation of objects related to this research. The Goods Distribution Information System is carried out by one of the administrative staff and is assisted by 2 (two) administrative, warehouse, and financial administration staff to record and input the distribution of goods. From the results of the study, it can be concluded that the Goods Distribution Information System has followed the procedure and uses a computer with Visual BASIC.NET programming language and Microsoft Access 2010 as its database.